A Review of Recent Studies on Cost Effectiveness of GHG Mitigation Measures in the European Agro-Forestry Sector - Carlo Giupponi; Francesco Bosello; Andrea Povellato (Fondazione Eni Enrico Mattei (FEEM), 2007)
Over the last twenty years, climate change has become an increasing concern for scientists, public opinions and policy makers. Due to the pervasive nature of its impacts for many important aspects of human life, climate change is likely to influence and be influenced by the most diverse policy or management choices. This is particularly true for those interventions affecting agriculture and forestry: they are strongly dependent on climate phenomena, but also contribute to climate evolution being sources of and sinks for greenhouse gases. This paper offers a survey of the existing literature assessing cost, effectiveness and efficiency of greenhouse gas mitigation strategies, or broader economic reforms, targeted to the agricultural and forestry sectors. The specific focus is on European Countries. Different methodological approaches, research questions addressed and results are examined. The main finding is that agriculture and forestry can potentially provide GHG reduction at a competitive cost. Nevertheless this cost is positive; accordingly, mitigation policies should be carefully designed either to balance costs with expected benefits or to avoid excessive penalisation of the sectors involved. Finally needs are highlighted for improving the existing knowledge and research methodologies.
Keywords: Q54; 330; Agriculture; Forestry; Climate Change; Greenhouse Gases; Policy Measures; Cost-Effectiveness; Meacap